Knowledge Management in Software Engineering Environments - Natali, Ana Candida Cruz; Falbo, Ricardo de Almeida (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2002)
Knowledge is one of the organization’s most important value, influencing its competitiveness. One way to capture organization’s knowledge and make it available to all their members is through the use of knowledge management systems. In this paper we discuss the importance of knowledge management in software development and we present an infrastructure to deal with knowledge management in software engineering environments (SEEs). This infrastructure is applied to manage product software quality knowledge in ODE, an ontology-based SEE.